Assessing the status of pinuchu as indicator of socio-ecological resilience of Chaya Socio-Ecological Production Landscape, Ifugao, Philippines - JHOANNA O. SANTIAGO; INOCENCIO E. BUOT, JR (Biodiversitas Journal of Biological Diversity, 2018)
Santiago JO, Buot Jr IE. 2018. Assessing the status of pinuchu as indicator of socio-ecological resilience of Chaya Socio-Ecological Production Landscape, Ifugao, Philippines. Biodiversitas 19: 2010-2019. Safeguarding biodiversity should be one of the priorities of the community to attain resilience. This study was aimed to determine the conditions of the woodlot (pinuchu) along the altitudinal zones of the mountain ranges in Chaya and correlated this to resilience. Specifically, it aimed to (i) determine the species composition, structure, and diversity of the tree species in selected pinuchu and (ii) determine the environmental variables associated with the vegetation composition. Vegetation data were subject to classification and ordination analyses. Species diversity was also calculated using Shannon-Wiener index. The tree diversity showed an overall diversity of (H'=3.83) corresponding to relatively high diversity. According to canonical correspondence analysis (CCA), elevation, temperature, and human disturbances influenced the vegetation composition. It is recommended that to sustain resilience of the CSEPL, pinuchu should be biodiversity-rich at all times. Policymakers should use native species as planting material in the reforestation program instead of using fast-growing exotic species.